Second Trimester Genetic Amniocentesis: Khon Kaen University 14-year experience - Thawalwong Ratanasiri; Ratana Komwilaisak; Teerayut Temtanakitpaisan; Saman Luengwattanawanit; Witoon Prasertcharoensuk; Piyamas Saksiriwuttho; Jamras Wongkam (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Objective: To evaluate the results of second trimester amniocentesis for prenatal diagnosis of chromosomal abnormalities at Khon Kaen University.Material and Method: A review of data from 2,825 genetic amniocenteses between January 1, 1993 and December 31, 2006 at Srinagarind Hospital,Faculty of Medicine,Khon Kaen University. Data reviewed included medical records, amniocentesis record forms and questionnaires sent by mail that inquired about complications and pregnancy outcomes. The mail out questionnaires response rate was 75.5%.Main outcome measure: Fetal loss rate after amniocentesis within 2 weeks.Results: The most common indication for genetic amniocentesis was advanced maternal age (90.7%). Chromosomal abnormalities were found 3.1%. The most common chromosomal abnormality was trisomy 21 (0.91%). The procedure failed in only one case (0.03%). Additional tapping was required in 1.29% of them. The culture failure rate was 2.01%. The fetal loss rate after amniocentesis was 0.6%.There were no significant differences in the factors affecting fetal loss that included maternal age, gestational age, placental puncture, operator, number of tappings, myoma uteri and color of amniotic fluid. Pregnancy outcome of the fetus with normal chromosomes included fetal death (0.3%) and preterm delivery (5.1%). Conclusion: Second trimester genetic amniocentesis at Khon Kaen University was a safe procedure in prenatal diagnosis of chromosomal abnormalities.